Perancangan Potensi Pemilihan Bibit Tanaman Obat Keluarga Dan Tanaman Hias Dengan Metode AHP Guna Menentukan Minat Masyarakat - Putri, Goldiffa Novinda; Mariana, Novita (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Plants are one of the living things that can grow anywhere, whether it's in the home environment, yard or garden, and even though the forest. Characteristics of plants are distinguished by type, namely, Trees, Medicinal Plants, Ornamental Plants, and Grass. Toga plant is a plant that functions for the treatment of diseases. While ornamental plants are plants that function to create beauty and attractiveness. The many benefits of plants, this further increases public interest. However, when people want to plant plants but do not understand what plants are suitable, a decision support system is made to assist in determining the types of plants that are suitable and at the same time determine the level of interest of the society based on five criteria, namely price, treatment method, quality, weather, and soil conditions. By using the calculation of the Analytical Hierarchy Process (AHP) method, the calculation is carried out by determining the pairwise comparison table, normalizing the pairwise comparison matrix and calculating the weight of each criterion. The results for the Toga plant, namely Pandan, were in first place with the highest weight value of 0.337692572 while for Ornamental plants, Aglonema was in first place with the highest weight value of 0.225819915.